2022
DOI: 10.1039/d2ob01545e
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Dideoxy-1,4-imino-d- andl-lyxitol-based inhibitors bind to Golgi α-mannosidase II in different protonation forms

Abstract: Development of effective inhibitors of Golgi α-mannosidase II (GMII, E.C.3.2.1.114) with minimal off-target effects towards the phylogenetically-related lysosomal α-mannosidase (LMan, E.C.3.2.1.24) is a complex task due to complicated structural and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 60 publications
0
10
1
Order By: Relevance
“…The enzymes screened included two Golgi types (GMIIb and AMAN-2) and two lysosomal types (LManII and JBMan) (Table 1). As for the Golgi-type mannosidases, AMAN-2 is a more relevant enzyme because its amino acid sequence and the 3D structure of its active site are almost identical to those of human GMII [22].…”
Section: Enzyme Assaymentioning
confidence: 99%
See 4 more Smart Citations
“…The enzymes screened included two Golgi types (GMIIb and AMAN-2) and two lysosomal types (LManII and JBMan) (Table 1). As for the Golgi-type mannosidases, AMAN-2 is a more relevant enzyme because its amino acid sequence and the 3D structure of its active site are almost identical to those of human GMII [22].…”
Section: Enzyme Assaymentioning
confidence: 99%
“…The resulting biochemical evaluation revealed that imino-ᴅ-lyxitols with N-substituents possessing a polar basic functional group (amidine or guanidine) were 6-7 times less active toward AMAN-2 than GMIIb and had poorer selectivities (SI below 35). In contrast, imino-ᴅ-lyxitols bearing a nonpolar N-arylalkyl chain (benzyl, p-iodobenzyl, 2-naphthylmethyl) showed slightly higher inhibitory activities toward AMAN-2 and good to excellent selectivities [22], indicating that they are more suitable candidates for the next-generation design of potent and selective GMII inhibitors.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations